PENGARUH DIMENSI BUDAYA NASIONAL TERHADAP RISIKO FRAUD (Studi Empiris pada 94 Negara) - Alfarin, Monika; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2021)
The increase of fraud cases constantly becomes a crucial problem for enterprises in the world. Anti-fraud program on companies needs holistic fraud risk input to be effective and efficient. Culture as an aspect of life is affecting every society. Then, the purpose of this research is to analyze the effect of culture on fraud risk. National culture dimension from Hofstede’s theory is used in this research. Dimensions that tested are power distance, individualism, masculinity, uncertainty avoidance, long-term orientation, and indulgence. The fraud risk is proxied by Corruption Perceptions Index 2020 (CPI 2020). Data population is 94 countries that had culture dimension and CPI 2020 measured. Data that had earned then tested with multiple linear regression method. The result of this research shows that power distance and masculinity give positive effect on fraud risk. On the other hand, long-term orientation, individualism, and indulgence dimension give negative effect to fraud risk.